Endothelin and the neurovascular unit in pediatric traumatic brain injury - Armstead, William M (2011)
OBJECTIVE: This study characterized the association between endothelin-1, cerebral hemodynamics, and histopathology after fluid percussion brain injury in the newborn pig. METHODS: Lateral fluid percussion injury was induced in newborn pigs equipped with a closed cranial window. Cerebral blood flow was determined with radiolabeled microspheres and cerebrospinal fluid endothelin-1 was measured by radioimmunoassay. RESULTS: Cerebrospinal fluid endothelin-1 was increased from 26 ± 4 to 296 ± 37 pg/ml (~10(−10)M) at 8 hours following fluid percussion injury. Post-injury treatment (30 minutes) with the endothelin-1 antagonist BQ-123 (1 mg/kg, intravenous) blocked pial artery vasoconstriction to topical endothelin-1 (~10(−10)M) and blunted fluid percussion injury-induced reductions in cerebral blood flow at 8 hours post-insult (56 ± 6 and 26±4 ml/minute versus 57 ± 6 and 40 ± 4 ml/minute; 100 g for cerebral blood flow before injury and 8 hours post-fluid percussion injury in vehicle and BQ-123 post-treated animals, respectively). Fluid percussion injury resulted in neuronal cell loss and decreased microtubule associated protein 2 immunoreactivity in the parietal cortex, which were blunted by BQ-123. DISCUSSION: These data indicate that fluid percussion injury-induced changes in cerebral hemodynamics are associated with neuronal damage and that endothelin-1 contributes to fluid percussion injury-induced histopathologic changes.